Prescription analysis and cost of antidepressant drugs in major depressive disorder outpatients at the tertiary care hospital of Pakistan: a prospective approach. (4th July 2022) - Kamran, Sohail; Khan, Zakir; Saqlain, Muhammad; Nazar, Zahid; Khan, Muska; Ali, Zulnorain; Rashid, Haroon; Shah, Kifayat Ullah; Karatas, Yusuf; Rahman, Najeeb Ur
ABSTRACT: Objectives: To assess prescribing care indicators, utilization pattern, cost per prescription, cost ratios, and percent cost variation of antidepressants (ADs). Method: A prospective cross-sectional study was carried out at the tertiary care hospital of Peshawar, Pakistan among major depressive disorder (MDD) outpatients from July 2019 to February 2020. The ideal standards for World Health Organization (WHO) prescribing care indicators were used. The ePharma Guide was used to calculate the cost in Pakistani rupees (Rs) and United States dollar (USD) 2021 (exchange rate: 1 USD = 154.43 Rs). Results: A total of 296 MDD patients received 846 drugs (average 2.86; range:1–8), of which 366 were ADs (average number ADs/prescription; 1.23). About 23% (n = 68) of patients received more than one AD. Only 21 (5.7%) generic ADs were prescribed, and 346 (94.5%) ADs were prescribed from the hospital formulary list. Selective serotonin reuptake inhibitors (SSRIs) were the most prescribed ADs (67.5%). The average cost of ADs per prescription per month was 700.95 Rs (4.54 USD). Escitalopram (5.69 Rs; 0.04 USD) showed highest cost ratio and maximum percentage cost variation (468.97%). Conclusion: This study observed low generic prescribing, a higher prescribing trend of SSRI, wide differences in cost ratio and percentage cost variation among ADs.